2010
DOI: 10.1002/jbmr.153
|View full text |Cite
|
Sign up to set email alerts
|

APC mutations are associated with increased bone mineral density in patients with familial adenomatous polyposis

Abstract: The canonical Wnt pathway plays a key regulatory role in osteoblastogenesis and bone mass acquisition through its main effector, bcatenin. Adenomatous polyposis coli (APC) represents the key intracellular gatekeeper of b-catenin turnover, and heterozygous germline mutations in the APC gene cause familial adenomatous polyposis (FAP). Whether APC mutations affect bone mass has not been previously investigated. We conducted a cross-sectional study evaluating skeletal status in FAP patients with a documented APC m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 45 publications
(46 reference statements)
2
13
2
Order By: Relevance
“…APC may also be a nucleocytoplasmic shuttle protein (350), which has been speculated to chaperone β-catenin out of the nucleus (351,352) and thus preventing β-catenin from binding to TCF/LEF (350,353,354). As a negative regulator of β-catenin, defects in or loss of APC results in increased bone mass: FAP patients with APC mutations within the β-catenin binding domains have increased bone mineral density (355).…”
Section: Adenomatous Polyposis Coli (Apc)mentioning
confidence: 99%
“…APC may also be a nucleocytoplasmic shuttle protein (350), which has been speculated to chaperone β-catenin out of the nucleus (351,352) and thus preventing β-catenin from binding to TCF/LEF (350,353,354). As a negative regulator of β-catenin, defects in or loss of APC results in increased bone mass: FAP patients with APC mutations within the β-catenin binding domains have increased bone mineral density (355).…”
Section: Adenomatous Polyposis Coli (Apc)mentioning
confidence: 99%
“…We focused on the role of Wnt signaling in this regard because the pathway is widely recognized as a key regulator of bone mass [29e31]. Experimental and clinical evidence both indicate that elevated Wnt signaling induces bone formation [32e34] whereas reduced Wnt signaling induces bone loss [35,36].…”
Section: Introductionmentioning
confidence: 99%
“…[47][48][49] Furthermore, the increase of bone mineral density in patients with FAP was described. 43,46 FAP patients displayed a significantly higher mean of bone mineral density compared with age and sex than healthy controls. These data suggested an activation of the Wnt pathway in heterozygous of APC mutations probably due to the regulation of β-catenin levels.…”
Section: Discussionmentioning
confidence: 88%
“…Recent studies have found the role of the Wnt pathway in tooth and bone development. [42][43][44][45][46][47] The expression of Wnt pathway was observed in the human oral epithelium during morphogenesis stages of the tooth development. 44 In addition, a study published in 2009 45 demonstrated in embryonic mice oral epithelium that the ablation of APC and activation of Wnt/β-catenin resulted in supernumerary tooth development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation